2011
DOI: 10.1007/s12265-011-9321-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Flow Left Ventricular Assist Device Support on Microvascular Endothelial Function

Abstract: The effects of continuous flow left ventricular assist device (CF-LVAD) support on microvascular endothelial function in New York Heart Association (NYHA) class IV heart failure (HF) patients are currently unknown. Microvascular endothelial function was assessed by beat-to-beat plethysmographic measurement of finger arterial pulse wave signal changes for 5 min following reactive hyperemia. A group of seven NYHA class IV HF patients was evaluated before CF-LVAD placement (HF), and a second group of six NYHA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Again, there appears to only be one other study, to date, that has evaluated the effects of continuous-flow LVAD support on microvascular function. In that study, Lou et al (38) reported that 1–4 months of LVAD support did not negatively affect microvascular function, as measured by the reactive hyperemia index, compared to a group of HFrEF patients that were awaiting LVAD implantation. These findings support the results of the current study, however, given the increased incidence of LVAD implantation as a destination therapy and the potential for vascular stiffening to occur with long-term ventricular support (39), further studies are necessary to better examine blood flow distribution and the consequences in the microcirculation with LVAD use.…”
Section: Discussionmentioning
confidence: 98%
“…Again, there appears to only be one other study, to date, that has evaluated the effects of continuous-flow LVAD support on microvascular function. In that study, Lou et al (38) reported that 1–4 months of LVAD support did not negatively affect microvascular function, as measured by the reactive hyperemia index, compared to a group of HFrEF patients that were awaiting LVAD implantation. These findings support the results of the current study, however, given the increased incidence of LVAD implantation as a destination therapy and the potential for vascular stiffening to occur with long-term ventricular support (39), further studies are necessary to better examine blood flow distribution and the consequences in the microcirculation with LVAD use.…”
Section: Discussionmentioning
confidence: 98%
“…18,19 Therefore, it is possible that factors contributing to sexual dysfunction with HF are not completely reversed during the LVAD support. Performance dysfunction (erectile dysfunction or vaginal dryness) was the most prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial progress has been made in understanding molecular and genetic changes following VAD[17], but much remains unknown. The impact of altered blood flow from CF-VAD on endothelial function is unclear[52], and improved understanding is likely to accelerate efforts to mitigate hematologic complications. Finally, studying patients whose heart failure is briskly and substantially reversed with mechanical circulatory support may offer insights into the pathophysiology of heart failure beyond the findings in this specific population.…”
Section: Discussionmentioning
confidence: 99%